Effect of maturation on wild apricot vermouth of different treatments - Abrol, Ghan Shyam (Array, 2019)
Wild apricot vermouths (WAV) of different sugar levels (8, 10 and 12 °Brix), different alcohol levels (15, 17 and 19%) and spice levels (2.5 and 5%) were prepared. The product was matured for six months and evaluated for physico-chemical characteristics at 0, 3 and 6 months of maturation. In general, ethyl alcohol content decreased in wild apricot vermouth of all treatments during maturation for six months, in proportion to their initial values. The decrease in TSS was revealed with the advancement of the storage period of six months. A similar trend was observed for total sugars with the advancement of the ageing period. The amount of reducing sugars, however, increased with the prolongation of the maturation period. The total esters content in WAV increased with the advancement of the ageing period, irrespective of their alcohol content. However, the volatile acidity showed a very little increase during ageing but remained non-significant among the different treatments. Total phenols content in WAV decreased by both the ageing period of six months and an increase in alcohol level. A non-significant increase in the titratable acidity with an ageing period was observed in all the WAV having different alcohol levels. The effect of spice extract levels added in the preparation of WAV showed that with the advancement of storage period total esters increased from 246.8 to 272.8 mg/L and 252.8 to 280.6 mg/L for WAV having 2.5 and 5% spices content, respectively. In brief, an overview of the entire results revealed that there was an interactive effect of alcohol level, the sugar level and the spice extract during maturation of wild apricot vermouth. It can be concluded that the maturation of WAV exerted a favourable effect on physico-chemical properties of wild apricot vermouth and is thus, considered desirable.